Kazakhstan Can Achieve Ambitious HIV Targets Despite Expected Donor Withdrawal by Combining Improved ART Procurement Mechanisms with Allocative and Implementation Efficiencies - Shattock, Andrew J. (PLoS, 2019)
Despite a non-decreasing HIV epidemic, international donors are soon expected to withdraw funding from Kazakhstan. Here we analyze how allocative, implementation, and technical efficiencies could strengthen the national HIV response under assumptions of future budget levels. We used the Optima model to project future scenarios of the HIV epidemic in Kazakhstan that varied in future antiretroviral treatment unit costs and management expenditure—two areas identified for potential cost-reductions.